Perancangan Sistem Informasi Instalasi Hemodialisa Pada Rumah Sakit Umum Daerah Karawang - Apit Priatna; Arif Maulana Yusuf; Anggi Elanda (Elkom : Jurnal Elektronika dan Komputer, 2021)
The use of information, media and communication technology has changed both the behavior of society and human civilization globally. The development of hospitals in Karawang is increasingly mushrooming, as well as the increasing number of degenerative diseases such as hypertension and diabetes, the increasing prevalence of chronic kidney disease. So it requires the handling of renal replacement therapy (Renal Replacement Therapy) because it is increasingly needed for cases of acute and chronic renal failure. The purpose of this research is to build an integrated and controlled information system that can simplify the patient administration process and reduce the effectiveness of the patient's time for dialysis. The methodology that the authors use in this study includes methods of identification and system design. System identification includes identification of the organization, running systems, and problem identification. The problems faced at this time in the Hemodialysis Installation. Patient data is not the same between patients who are served by hemodialysis (dialysis) and those in the application report, the transaction value for using tools and materials is sometimes empty or there is no transaction value in the application, it will cause losses to the customer. hospital. It is hoped that this system can eliminate the problems that have been happening so far.